Parking Service & Hospitality Aspect : Learn from Malioboro, Yogyakarta - Yorri Kusuma Nugraha; Siti Sumaryatiningsih (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2023)
The special region of Yogyakarta has diverse tourist attractions, including the famous Malioboro area, despite its small size. Malioboro has been a cultural tourism hotspot since the early 1800s, offering delicious food, historical sights, and cultural arts performances. As a result, Malioboro attracts a lot of tourists who require adequate parking facilities. However, an issue has arisen regarding the imposition of coercive parking fees, which has garnered significant attention on social media platforms and negatively impacted tourists' satisfaction. This study presents an immediate and medium-term solution to the parking problem faced by tourists in Malioboro, Yogyakarta. Immediate measures include conducting regular inspections and enacting laws to prevent parking violations by businesses. In the medium term, the study recommends the introduction of electronic parking systems to minimize direct contact and enable integrated monitoring by operators and municipalities. These measures are aimed at improving the park experience, restoring trust and boosting Yogyakarta's reputation as a popular tourist destination. This study contributes to the destination management literature by highlighting the importance of resolving parking issues to provide a pleasant experience for tourists in Malioboro and similar locations. The results provide valuable insights for policy makers, tourism authorities and parking operators to develop effective strategies to manage parking facilities and increase visitor satisfaction.